CALCULATION METHOD OF WOMEN’S VOLLEYBALL ATHLETE ININ PERKASA JAYA CLUB BLITAR CITY - Laurina Dea Augustine; Diana Elvianita Martanti (Universitas Islam Balitar, 2020)
This research aims to determine and describe the women’s volleyball athletes contract calculation method of Perkasa Jaya, Blitar City. The research method uses qualitative method of the phenomenologist approach. Data collection techniques in this study through observation, interviews, and literature study. The results showed that there were several factors that influenced the calculation method, namely the ability of players, experience of competition, teamwork, and the position of players in the team. These factors are related to the size of the athlete's contract and consideration of the contracting party. So, each player has a different contract value. The Perkasa Jaya Club has provisions for club members who regulate cooperation with other parties. The contract calculation method will enter the club's cash at 30% of the monthly salary so that the athlete only receives 70% of the salary earned. Other salaries such as competition salaries, bonuses or others will not be deducted by the club. All rules and regulations that are regulated to members have been notified to new members before joining the Perkasa Jaya club. Before entering into contracts with other parties or other clubs, players also make a statement so they do not feel aggrieved over the provisions that have been made by the Perkasa Jaya club